Castanea sativa Mill. bark extract cardiovascular effects in a rat model of high‐fat diet. (8th December 2020) - Micucci, Matteo; Budriesi, Roberta; Aldini, Rita; Fato, Romana; Bergamini, Christian; Vivarelli, Fabio; Canistro, Donatella; Bolchi, Cristiano; Chiarini, Alberto; Rizzardi, Nicola; Pallavicini, Marco; Frosini, Maria; et al.
Abstract : Ellagitannins may have a beneficial impact in cardiovascular diseases. The aim of the study was to evaluate the effect of high‐fat diet (HFD) and the efficacy of Castanea sativa Mill. bark extract (ENC) on cardiac and vascular parameters. Rats were fed with regular diet, (RD, n = 15), HFD ( n = 15), RD + ENC (20 mg/kg/day by gavage, n = 15), and HFD + ENC (same dose, n = 15) and the effects on body weight, biochemical serum parameters, and inflammatory cytokines determined. Cardiac functional parameters and aorta contractility were also assessed on isolated atria and aorta. Results showed that ENC reduced weight gain and serum lipids induced by HFD. In in vitro assays, HFD decreased the contraction force of left atrium, increased right atrium chronotropy, and decreased aorta K + ‐induced contraction; ENC induced transient positive inotropic and negative chronotropic effects on isolated atria from RD and HFD rats and a spasmolytic effect on aorta. In ex vivo experiments, ENC reverted inotropic and chronotropic changes induced by HFD and enhanced Nifedipine effect more on aorta than on heart. In conclusion, ENC restores metabolic dysfunction and cardiac cholinergic muscarinic receptor function, and exerts spasmolytic effect on aorta in HFD rats, highlighting its potential as nutraceutical tool in obesity.